ANALISIS SURVIVAL KEJADIAN LOSS TO FOLLOW-UP TERAPI ANTI- RETROVIRAL (ARV) PADA PASIEN HIV DI KOTA SAMARINDA: LOSS TO FOLLOW-UP TERAPI ANTI- RETROVIRAL - Utami, Dian Margi; Wisnuwardani, Ratih Wirapuspita; Saefurrohim, Muhamad Zakki (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Loss to follow (LTFU) -up among HIV patients, defined as failure to continue therapy as schduled,increases the risk of drug resistance, deteriorating health conditions, and death due to HIV-relatedcomplications. This study aimed to analyze the survival of HIV patients againts LTFU events amongthose undergoing antiretroviral therapy (ARV) in Samarinda City. Secondary data from the SIHAdatabase (2023-2024) were utilized. Kaplan-Meier analysis was applied to evaluate the factors ofgender, residence, population group, and timing of ARV initiation associated with the risk of LTFU.The results showed that gender and residance were not significantly associated with the risk of LTFU.However, specific population groups, such as children of PLHIV and pregnant women, exhibitedhigher vulnerability and lower survival rates (log rank = 0.015). ART initiation within ≤ 1 monthsignificantly improved survival probability compared to initiation after > 1 month. These findinghighlight that while gender and residance do not significantly influence LTFU, the vulnerability ofspesific populations and the critical importance of early ART initiation are key factors. It isrecommende to develop targeted interventions focusing on vulnerable groups, such as children ofPLHIV and pregnant women, to enhance their survival rate. Additionally, strategies promoting ARTinitiation within ≤ 1 month are esential to improve treatment sustainability.